Evaluation of Anti-Helicobacter pylori Antibodies in A group of Iraqi Patients with Atherosclerosis and Coronary Artery Disease - K. Ismael, May; R. Al-Haleem, Mahmood; S. Salman, Rawaa (Iraqi Journal of Science, 2023)
Evaluation of Anti-Helicobacter pylori Antibodies in A group of Iraqi Patients with Atherosclerosis and Coronary Artery Disease